ドイツ ノ ナンキョク カンソク カツドウ - 白石, 和行; シライシ, カズユキ; Shiraishi, Kazuyuki (1997)
P(論文) 各国の南極観測は, それぞれの国情を反映してさまざまな形態で実施されている。ある国の採用している南極観測事業の方法や制度は必ずしも他の国の観測隊にとって有効ではないが, 外国の南極観測の情報は日本の南極観測事業の向上にとって有益であろう。筆者は1997年1月から3月まで, 交換科学者としてドイツの南極観測隊に参加する機会を得た。わが国の観測事業に資するために, ここで得た, ドイツの南極観測事業の現状と現場での活動の情報を紹介する。 The methods of Antarctic expeditions are different from country to country in terms of scale of the expedition, organization, funding, geographical situation of the area of activity and so on. Although methods used by one country are not always adaptable to other countries, information on foreign countries' Antarctic programs would provide ideas to contribute to upgrading the Japanese Antarctic Research Expedition (JARE). The author participated in the German Antarctic Expedition in the 1996-97 field season. The author's participation was focussed on the transportation system, air operation and inland traverses. This report summarizes the activity of the German Expedition and highlights some aspects which should be incorporated into JARE. departmental bulletin paper